Optimization of Fenton Process for Treatment of Amoxicillin, Ampicillin and Cloxacillin Antibiotics in Aqueous Solution - Elmolla, E.; Chaudhuri, M. (Elsevier, 2009)
The study examined the effect of operating conditions of the Fenton process on biodegradability improvement and mineralization of amoxicillin, ampicillin and cloxacillin antibiotics in aqueous solution. In addition, degradation of amoxicillin, ampicillin and cloxacillin under optimum operating conditions were evaluated. The optimum operating conditions for an aqueous solution containing 104, 105 and 103 mg/L amoxicillin, ampicillin, and cloxacillin, respectively were observed to be COD/H2O2/Fe2+ molar ratio 1:3:0.30 and pH 3.Under optimum operating conditions, complete degradation of amoxicillin,ampicillin and cloxacillin occurred in 2 min. In addition, biodegradability improved from ∼0 to 0.37 in 10 min, and COD and DOC degradation were 81.4% and 54.3%, respectively in 60 min. Maximum biodegradability (BOD5/COD ratio) improvement was achieved in 10, 20 and 40 min at antibiotics concentration 100, 250 and 500 mg/L, respectively for each antibiotic in aqueous solution. Increase in nitrate and ammonia concentration were observed due to mineralization of organic nitrogen, concentration of nitrate increased from 0.3 to 10 mg/L and concentration of ammonia increased from 8 to 13 mg/L in 60 min. The study indicated that Fenton process can be used for pretreatment of amoxicillin, ampicillin and cloxacillin wastewater for biological treatment.